2016
DOI: 10.1007/s40273-016-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

NETIMIS: Dynamic Simulation of Health Economics Outcomes Using Big Data

Abstract: Many healthcare organizations are now making good use of e-health record (EHR) systems to record clinical information about their patients and the details of their healthcare. Electronic data in EHRs is generated by people engaged in complex processes within complex environments and their human input, albeit shaped by computer systems, is compromised by many human factors. This data is potentially valuable to health economists and outcomes researchers but is sufficiently large and complex enough to be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This research used secure links to the Leeds General Infirmary Information System with data from 3 million secondary and tertiary care patients. A dynamic modeling tool called NETIMIS (Network Tools for Intervention Modeling with Intelligent Simulation) was developed to visualize both human-developed and derived AI that could be used for what-if analysis by stakeholders to determine cost, and to develop and evaluate medical interventions [28]. An additional study on the use of dynamic simulation models of BD in healthcare has described the mutually beneficial synergy between BD and these models.…”
Section: The Role Of Bd In Healthcarementioning
confidence: 99%
“…This research used secure links to the Leeds General Infirmary Information System with data from 3 million secondary and tertiary care patients. A dynamic modeling tool called NETIMIS (Network Tools for Intervention Modeling with Intelligent Simulation) was developed to visualize both human-developed and derived AI that could be used for what-if analysis by stakeholders to determine cost, and to develop and evaluate medical interventions [28]. An additional study on the use of dynamic simulation models of BD in healthcare has described the mutually beneficial synergy between BD and these models.…”
Section: The Role Of Bd In Healthcarementioning
confidence: 99%
“…Data limitations were identified in ten papers [20], [22], [33], [36], [37], [44], [48], [57], [60] and were mostly related to limited access to the data, data quality problems, attributes not available in the data being extracted, or the dataset available in inappropriate level of details. Technique limitations were identified in 13 papers [3], [21], [28], [31], [35], [38]- [40], [48], [50], [52], [63], [64] specifically if the study undertaken was done by implementing plug-ins/ functionalities available in tools. Team limitations were identified in two papers [11], [23] because the authors realize that they need medical domain experts to be included in the research team.…”
Section: F Limitations and Future Workmentioning
confidence: 99%
“…Our previous literature review found that process mining has been used in oncology and shows promising results to support process analytics [ 8 ]. In earlier work with the Leeds Cancer Centre data [ 9 , 10 ], we had assumed that there were no changes to the process during the time period. We were aware that the period was long, that the organisation, system, and people had evolved and changed over time, but we were not aware of specific process changes before we commenced the study.…”
Section: Introductionmentioning
confidence: 99%